(untitled) (Analysis in Theory and Applications, 2017)
In this paper, we prove the boundedness of the fractional maximal operator, Hardy-Littlewood maximal operator and marcinkiewicz integrals associated with Schrödinger operator on Morrey spaces with variable exponent.